Exploring the untapped potential of naturally occurring antimicrobial compounds: novel advancements in food preservation for enhanced safety and sustainability - Karnwal, Arun; Malik, Tabarak (Frontiers in Sustainable Food Systems, 2024)
Current research trends emphasize the strategic utilization of natural and renewable resources, specifically within food and medicine, focusing on naturally occurring antimicrobial compounds. While growing interest is in extracting secondary metabolites from plants, bacteria, and enzymes, a substantial portion of these naturally derived molecules remains inadequately explored. These antimicrobial agents exhibit heightened safety compared to their synthetic counterparts, posing no health risks to consumers. This presents an opportunity to replace perilous synthetic chemicals within the food sector. Despite the increasing popularity of natural additive sources, there is a potential for adverse effects on product sensory qualities. Therefore, notwithstanding recent advancements, further investigation is imperative to optimize effective quantities for the successful inhibition of pathogenic microorganisms. This article delves into pioneering developments in food preservation, offering contemporary insights into natural preservation solutions, especially for perishable commodities.